Preclinical hematological profile studies of an ayurvedic medicine Siddha Makardhwaja after chronic administration to male sprague-dawley rats - Sikder, Md. Mamun; Chakraborty, Proshanta; Mahbub, Md. Ruhul; Zulfiquar, Tasniya Nahiyan; Neon, Md. Nuruzzaman; Saha, Nilay; Chowdhury, Imtiaj Hossain; Choudhuri, M.S.K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Siddha Makardhwaja (SMD) is a classical Ayurvedic formulation markedly used as a traditional medicine in the rural population for various purposes such as stimulant, tonic, and rejuvenator. Methods: The present study is conducted to evaluate the effect of conventionally prepared SMD on the hematological parameters in experimental animals, for providing scientific data base for its logical use in clinical practice. Acute toxicity tests were conducted to determine the LD50 of the drug. To find out the effect of chronic administration of SMD on hematological parameters it was administered chronically to the male Sprague-Dawley rats at a dose of 40mg/kg for 28 days. Results: In this experiment the TC, DC, various erythrocytic parameters, platelet parameters, ESR were determined. The results of the studies are given below. There is an (13.41%) increase in the number of white blood cell count of the male rat, the increase though not significant yet it was prominent (p=0.257). There is an (15.87%) increase in the absolute count of Neutrophils of the male rat, the increase though not significant yet it was prominent (p=0.371). There is an (12.29%) increase in the absolute count of Lymphocytes of the male rat, the increase though not significant yet it was prominent (p=0.388). There is a statistically significant (p=0.035) increase in the number of platelet count of the male rat (11.13% increase). There is a (2.03%) decrease in the platelet volume distribution width of the male rat, the decrease though not significant yet it was noticeable (p=0.094). There is a statistically insignificant (p=0.619) (10.0%) increase in Erythrocyte sedimentation rate in blood from the male rat. Conclusions: As SMD decreases and increases abnormally on the hematological parameters in body of treated rats, so it should not be administered chronically at a higher dose. Further studies should be done by reducing the administered dose.